PowerPoint - Len Proctor (The Canadian Network for Innovation in Education (CNIE), 1990)
Capturing the interest of viewers is a first priority item among teachers and other professionals who use media in their presentations. PowerPoint, one of the growing number of PC slide programs becoming available, is one more tool that can be used to achieve this goal. While this program was not intended to replace a graphic artist, it does give the ordinary presenter the ability to create professional looking slides. And, as a fringe benefit, control over the content, sequence and production time has been returned to the user.